COVID-19 and Regional Security. Global Macrosecuritization, Local Adaptations, and the Dilemmas of Latin American Cooperation - Dalponte, Bruno (2021)
This article analyses the main lines around which the securitization of COVID-19 has been interpreted and used in Latin America. Starting from an understanding of securitization that incorporates a dialogue between the local and the global to interpret the specific characteristics of the process, the investigation observes the varied ways in which different countries in the region have adapted global security discourses. The main global security dynamics around COVID-19, the particularities of its main local counterparts, and the extraordinary actions legitimized as a result of them are analysed. It is argued that the variations in the constructions of the “pandemic threat” by regional actors, carried out in isolation and read through different interpretive frameworks, are both a consequence and an aggravating factor of political disagreements between national leaders. In this way, the article seeks to make a general balance that serves as the basis for continuing the debate on the many aspects in which the current pandemic has affected regional security.